ESTIMASI HARGA OBLIGASI MENGGUNAKAN PENDEKATAN DURASI DAN KONVEKSITAS HEATH JARROW MORTON DARI UKURAN SENSITIVITAS HARGA OBLIGASI TERHADAP YIELD (Studi Kasus : Obligasi Pemerintah Indonesia) - , FEBTIO ADI WIBAWANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bonds as invesment instrument are classified in fixed income securities have risks from changes in yields. In this case, investors require bonds for risk management to minimize the risks resulting from change in yields amd obtain the desired return. Duration and convexity are used in a suitable combination of risk management. Approach duration and convexity Heath Jarrow Morton for coupon bonds are one way to sensitivity measure of bond price introduced by Manfred Fruhwirth (2001) with two popular examples of HJM models with deterministic volatility structure. They are constant volatility model (Ho/Lee, 1986) and exponential volatility model (Hull/White, 1990). In this graduation paper will be discussed how to calculate the duration and convexity Heath Jarrow Morton with constant volatility model to estimate bond price changes more accurate from change in yields by comparing the estimated price of the bond using traditional approach and exponential approach in yield contionuous time. Furthermore, constructing the weight/proportion of optimal bonds to form bond portfolio with moment method.